2017
DOI: 10.1111/crj.12640
|View full text |Cite
|
Sign up to set email alerts
|

Role of monocyte tissue factor on patients with non‐small cell lung cancer

Abstract: Monocyte TF may be a relevant source of TF-mediated thrombogenicity in NSCLC patients and may be associated with prognosis in NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Among patients with lung cancer, TF expression in circulating monocytes of patients with VTE was higher than that in patients without VTE. 45 Our findings suggest that monocyte/macrophage TF expression in thrombi is enhanced in patients with cancer. The higher frequency of TF-positive monocytes/macrophages may be affected by enhanced organization in cancer-associated VTE ( Table S6 ) since the number of macrophages increased in a time-dependent manner in DVT.…”
Section: Discussionmentioning
confidence: 60%
“…Among patients with lung cancer, TF expression in circulating monocytes of patients with VTE was higher than that in patients without VTE. 45 Our findings suggest that monocyte/macrophage TF expression in thrombi is enhanced in patients with cancer. The higher frequency of TF-positive monocytes/macrophages may be affected by enhanced organization in cancer-associated VTE ( Table S6 ) since the number of macrophages increased in a time-dependent manner in DVT.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies showed that invasive metastasis was signifcantly associated with high expression of VEGF in solid tumors, such as hepatocellular carcinoma and colorectal cancer [17,18]. Guo et al [19] and Deng et al [20] confrmed that VEGF levels were closely associated with DLBCL, serum VEGF levels were highly expressed in patients with DLBCL, and correlated with LDH levels and histological types. It has been used as an important indicator for evaluating the prognosis of DLBCL due to the lack of clear diagnostic and prognostic indicators for DLBCL [21].…”
Section: Discussionmentioning
confidence: 95%
“…In a study with respect to venous thrombosis in resected specimens for non-small cell lung cancer (NSCLC), 53.6% of cases with thrombosis were accompanied by tumor vascular infiltrating [ 25 ]. Another prospective study suggested monocyte tissue factor (TF) that was a source of TF-mediated thrombogenicity in NSCLC patients was significantly higher in patients with lymph node metastasis than those without lymph node metastasis [ 26 ]. In addition, for patients with advanced NSCLC, VTE development is associated with a previous history of VTE [ 27 ].…”
Section: Discussionmentioning
confidence: 99%